Seroconversion dynamics of bovine viral diarrhea and neosporosis in dairy herds of the central highlands of Peru - Arauco Villar, Fernando (2020)
The aims of this study were to determine the dynamics of seroconversion of bovine viral diarrhea (DVB) and neosporosis, as well as the presence of animals persistently infected (PI) with the DVB virus in cattle farms of two experimental stations of the Universidad Nacional del Centro del Peru: In total, 111 Brown Swiss cattle in the EEA El Mantaro and 39 Holstein cattle in the GA Yauris, both located in the central highlands, Junín Region, Peru were used. Three evaluations (August 2015, and February and August 2017) were performed to detect serum antibodies against vBVD and N. caninum, and DVB antigens, using ELISA tests. The average prevalence of DVB in the EEA El Mantaro was 73.5%, the seroconversion dynamics in the herd was increasing over time, and the prevalence of PI animals was 5.4%. For GA Yauris, the average prevalence of DVB was 16.67%, the seroconversion dynamics were stable over time, and the prevalence of PI animals was 2.78%. The prevalence of neosporosis in the EEA El Mantaro was 11.8%, with an increasing but moderate seroconversion dynamic, while in GA Yauris it was 36.81% with an increasing seroconversion dynamic in the last evaluation.